2021
DOI: 10.1111/cobi.13802
|View full text |Cite
|
Sign up to set email alerts
|

Use of environmental DNA in assessment of fish functional and phylogenetic diversity

Abstract: Article impact statement: Environmental DNA can be used effectively to survey taxonomic, functional, and phylogenetic diversity of tropical reef fishes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 86 publications
4
22
0
Order By: Relevance
“…This result can be considered as conservative since the spatial extent of the eDNA sampling is smaller than that of UVC so we could expect even more fish diversity detected with a more widespread eDNA sampling. This result is also consistent with many studies comparing sampling methods (Polanco Fernández et al 2021, Marques et al 2021). However, the incompleteness of reference databases limits the taxonomic assignment of eDNA sequences (Marques et al 2020a, Polanco Fernández et al 2021.…”
Section: Discussionsupporting
confidence: 92%
“…This result can be considered as conservative since the spatial extent of the eDNA sampling is smaller than that of UVC so we could expect even more fish diversity detected with a more widespread eDNA sampling. This result is also consistent with many studies comparing sampling methods (Polanco Fernández et al 2021, Marques et al 2021). However, the incompleteness of reference databases limits the taxonomic assignment of eDNA sequences (Marques et al 2020a, Polanco Fernández et al 2021.…”
Section: Discussionsupporting
confidence: 92%
“…Functional and phylogenetic characteristics are expected to offer higher dimensions of information to describe and manage ecosystems (Strecker et al, 2011). Coupling ecological indices with eDNA can provide more complete ecosystem information for coral reefs (Aglieri et al, 2021; Marques et al, 2021). As demonstrated previously with UVC (D'Agata et al, 2014), we found that functional and phylogenetic indices better discriminate between the two inventoried coastal areas than taxonomic information alone.…”
Section: Discussionmentioning
confidence: 99%
“…The massive amount of DNA sequence data from eDNA metabarcoding could be compounded into ecological indices, where the cumulated species‐specific responses translate into measures of environmental quality (Cordier, 2020). Furthermore, by combining with functional traits (e.g., including body size and trophic level) or phylogenetic information (Keck et al, 2018; Marques et al, 2021), eDNA could generate proxies of ecosystem structure and functioning more informative than those from taxonomic lists alone (D'Alessandro & Mariani, 2021). The use of functional or phylogenetic indices should be first evaluated along contemporary gradients of anthropogenic pressures before future application in monitoring of assemblages (Carvalho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRUVS offer an opportunity in this regard, as the video systems can be rapidly deployed at the exact location where eDNA is being sampled, while the bait may attract individuals in the vicinity that were also captured in the eDNA signal. Comparisons between eDNA and BRUVS have so far focused on biodiversity and community assessments (Boussarie et al, 2018; Jeunen, Lamare, et al, 2020; Marques et al, 2021; Mercaldo‐Allen et al, 2021; Stat et al, 2019), yet potential correlations between species‐specific qPCR detection and abundances recorded from BRUVS remain, to the best of our knowledge, untested.…”
Section: Introductionmentioning
confidence: 99%